South Sudan Economic Update, 2017 : Taming the Tides of High Inflation - World Bank (Washington, DC, 2017)
The Republic of South Sudan emerged in 2011 from decades of conflict as the world’s newest independent country, with huge state and peace building challenges, and extreme institutional and socio-economic deficits.By August 2016, South Sudan displayed all the signs of macroeconomic collapse,with output contracting, and inflation and parallel exchange market premium spiraling.The fiscal deficit remained high, although its exact magnitude is difficult to estimate given the lack of real time data.The financing situation is dire. Monetization of the fiscal deficit explains to a large extent the high inflation, although there are some indications that borrowing from theBank of South Sudan had been limited in recent months.The current account deficit is estimated to have narrowed to about 1.6 percent in FY2016/17 from about 6.1 percent of GDP in FY2015/16.The South Sudanese Pound (SSP) continued to depreciate.Restoring peace, including reform of the security sector, followed by efforts to rein in public sector borrowing to levels that avoid printing money are necessary preconditions for any stabilization program.The FY17/18 National Budget aims to restore macroeconomic stability, but lacks credibility.Even if the economy showed some recovery starting in 2018, projections suggest that poverty will continue to rise through 2019 as economic growth is likely to be surpassed by population growth.